PENGARUH MODEL PEMBELAJARAN THE LEARNING CELL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMP NEGERI 6 TORGAMBA - Eva Julyanti; Siti Nurintan (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2020)
This study aims to determine the effect of the learning cell learning model on the mathematical communication skills of VIII grade students of SMP Negeri 6 Torgamba. This research includes quantitative research. The population in this study amounted to 160 students. The sample in this study was class VIII-A and VIII-B, each with 32 students. The sampling technique used in this research is cluster random sampling, which is the taking of sample members from the population by randomizing classes. The results of this study indicate that the sig value in the regression analysis is 0,000. This value is less than 0.05 so that Ho is rejected and Ha is accepted. The decision is that there is an effect of the learning cell learning model on the mathematical communication skills of students of class VIII SMP Negeri 6 Torgamba. The effect of the learning cell learning model on the mathematical communication skills of students of class VIII SMP Negeri 6 Torgamba was 72.1%.